A sword scabbard chape with a depiction of a bird of prey from the surroundings of Kostrzyn - Michalak, Arkadiusz; Socha, Krzysztof (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2017)
In 2016, an Early Medieval sword scabbard chape was handed over to the Museum of Kostrzyn Fortress. According to the person submitting it, it was found about 5-6 years earlier in the northern part of Kostrzyn nad Odrą. The main decorative motif of the openwork field is a heraldically arranged bird. The closest analogies to the chape in question are dated to the second half of the 10th and 11th century. Artefacts of this type could have been produced in Scandinavia, but also in the Rus and Baltic areas. Unfortunately, we are not able to say what raw material was used to cast the artefact in question. An analysis of the metal composition of the find carried out on the surface of the artefact demonstrated that a very heterogeneous lead alloy was used, which could have also been a result of lead-bleaching. The same technology was also observed on the chapes from Ruthenia. Scholars have explained the presence of an ornithomorphic motif on the surface of the artefact in various ways